Analysis of the transcriptomic profiles of Mandarin fish (Siniperca chuatsi) infected with red sea bream iridovirus (RSIV). (January 2023) - Zhang, Yanbing; Zhang, Chunjie; Zhang, Zheling; Sun, Wei; Zhang, Xiaojun; Liu, Xiaodan
Abstract: Red sea bream iridovirus (RSIV) belongs to the family Iridoviridae, genus Megalocytivirus, which could widely infect marine fish, causing diseases and huge economic losses. Now it has been reported that RSIV was also detected in diseased mandarin fish. Transmission electron microscopy and immunohistochemistry showed that spleen was the main target organ in mandarin fish infected with RSIV. To investigate the immune response mechanism of mandarin fish to RSIV infection, transcriptomics of RSIV-infected mandarin fish was analyzed. A total of 53, 040 unigenes were obtained, and there were 21, 576 and 17, 904 unigenes had significant hit the Nr and SwissProt databases, respectively. In RSIV-infected and non-infected spleen tissues, there were 309 differentially expressed genes (DEGs), including 100 up-regulated genes and 209 down-regulated genes. Gene Ontology database (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analysis were performed to reveal the function information and give a better understanding of the signal transduction pathways of DEGs. Further analysis of the cytokine-cytokine receptor interactions pathway exhibited that the expression of cytokines was widely activated after viral infection. In addition, ten DEGs were randomly selected and verified by quantitative real-time PCR, which revealed a similar expression tendency as the high-throughput sequencing data. These findings present valuable information that will benefit for better understanding of RSIV infection in mandarin fish. Highlights: Spleen was the target organ with the highest viral content in mandarin fish infected with RSIV. Transcriptome analysis in the spleen of mandarin fish against RSIV infection was reported for the first time. A series of inflammatory factors and pathways that closely related to the host immune response were identified.